Velvet Antler Ameliorates Cardiac Function by Restoring Sarcoplasmic Reticulum Ca2+-ATPase Activity in Rats With Heart Failure After Myocardial Infarction - Shi, Haoyue; Zhao, Tianzi; Li, Yanjun; Xiao, Xiang; Wu, Jiayun; Zhang, Haojun; Qiao, Jiajun; Huang, Li; Li, Lin (Frontiers in Pharmacology, 2021)
Objective: Velvet antler (Cornu Cervi Pantotrichum, Va) , one of the most famous Chinese traditional medicine, has been shown to have cardioprotective effects. The purpose of this study was to investigate the effect of Va on heart failure caused by ischemia-reperfusion, and explore its possible mechanism from the regulation of sarcoplasmic reticulum Ca2+-ATPase (SERCA2a). Methods: Rat heart failure model was established by ligating male Sprague-Dawley (SD) rats’(n=88) left anterior descendingcoronary artery. One week after surgery, Va (200, 400 or 800 mg/kg/d) or enalapril (1 mg/kg/d) was daily administrated for the next 4 weeks. Heart function was detected by echocardiography and the histological pathological analysis. Serum BNP level was measured by ELISA, and the expressions of SERCA2a, PLB, PLB-Ser16 and PKA were determined by Western blotting. SERCA2a and PLB mRNA level were determined by RT-PCR. Results: Compared to Sham group, the cardiac function in HF group, including serum BNP level, HMI, myocardial collagen deposition, together with left ventricular ejection fraction (LVEF)was decreased notably. All the aforementioned changes were reversed by Va treatment. In addition, Va at low dose inhibited the decrease of SERCA2a, PLB mRNA level, SERCA2a, PLB, PLB-Ser16 and PKA expression, as well as restored the activity of SERCA2a and PKA. Enalapril affected only PLB protein expression. Conclusion: Va can improve myocardial fibrosis and ventricular remodeling in rats, thereby helping to restore cardiac function. The mechanism may be related to up-regulating the expression and activation of PKA and PLB and restoring the expression and activity of SERCA2a.